The impact of COVID-19 on tourism: Analysis of online reviews in the airlines sector - Rita, P. (2022)
This research aimed to understand how airline companies are addressing the crisis generated by the Covid- 19 pandemic and handling issues like cancellations and customer (dis)satisfaction. Research on online reviews from the most popular tourism website, TripAdvisor, was conducted through the collection of review posts from the leading 10 worldwide airline groups by number of passengers. These reviews were extracted from the sector’s most impacted period during the pandemic – from the date where the first travel restrictions were imposed until the date where they began to be lifted again (from March to May 2020), which consequently led to a greater number of posted and shared reviews. A total of 885 reviews were collected and analysed with the help of the Python-based sentiment analysis tool VADER. Results showed a very negative trend, which was mainly caused by issues related to refund policies and process, confirming the reported pandemic impact on this sector. Low-cost airlines revealed a lower customer satisfaction rate when compared to traditional ones, while most of the posts were related to Loyalty/Competitiveness, which affected brands’ overall equity. This study enables to better understand, from the customers’ perspective, how airlines were able to deal with the severe impact of the COVID-19 pandemic. Through such knowledge and subsequent critical discussion, we unveil the critical issues that have led to unsatisfied customers, helping to build up the body of knowledge on airlines’ recovery after the pandemic.